The Role of NOD-like Receptors in Recognition of Pathogen-associated Molecular Patterns of Infectious Pathogens and in Development of Inflammation. Part 2. NLR Family Proteins Involved in the Activation of RIP2-associated Signaling Pathway - A.Ye. Abaturov; A.P. Volosovets; Ye.I. Yulish (Zaslavsky O.Yu., 2013)
The review deals with the value of NLR (NLRC1/NOD1 and NLRC2/NOD2) in recognition of PAMP bacterial agents.